Implementasi Kebijakan Penanggulangan Banjir (Studi Kasus Proyek Normalisasi Banjir Kanal Barat dan Kali Garang Kota Semarang) - Putri Widyanti; Kismartini Kismartini; Maesaroh Maesaroh (Journal of Public Policy and Management Review, 2014)
Normalization Banjir Kanal Barat dan Kali Garang is one of three components flood control taken government to flood control annually almost always in some areas in the city of Semarang. The purpose of Normalisasi Banjir Kanal Barat dan Kali Garang itself is to increase the capacity to accommodate so as to discharge of water from the river is three times Kreo, Kripik and Garang. The aim of this research is trying to answer questions about Normalisasi Banjir Kanal Barat dan Kali Garang and analyzes factor supporting and inhibitors. Research methods used in this research using a qualitative research with methods of descriptive qualitative, which aims to describe explained and analyzed The work of normalization work is conducted by Balai Besar Wilayah Sungai Pemali-Juana by the contractor would work, Brantas Abipraya and Wijaya Karya Joint Operation and consultan inspectorship CTIE and associated. And departement. of PSDA an ESDM to creating land project. In construction work normalization begins november 2010 and to be completed in november 2013. After normalization Normalisasi Banjir Kanal Barat dan Kali Garang, so far the flood canal the west has been able to improve the capacity of a discharge of water which had been 300-400 m3/second to 730m3/second, flood control, other than a benefit this normalization of benefits in social sector, economy, the environment and for cultural city people Semarang especially. Supporting factors and inhibitors of the implementation of this protocol identified through five Adil Najam that is, namely content, context, commitment, capacity, and client and coalition of stekeholder involved, namely the government, private and public. Of the net content, Normalisasi Banjir Kanal Barat dan Kali Garang perceived capable of being a response to the issue of floods in society. But normalization this is not the only way to control the flood, there should be support the optimization of the function drainages the city. In context there have been the division of tupoksi clear between implementor, it's just coordination they do sometimes take a long time, and less efficient hence there must be a good time managent. Commitment, of the net private sector (contractors) has been able to reach its commitments to finish the job on time while the government in the provision of compensation tali asih is deficient according to the rules imposed so in the future needed the system controls more restrictive. In capacity, implementor of the policy is, who competent as Balai Besar Wilayah Sungai and great contractors. And to the factors of client and coalitions, actually either the government, private, community support each other, but here, public awareness to maintain clean environment is still less so fore requires explicitness the rules of the government in giving sanctions on those who do not pro-activ in keeping clean environment.